2015
DOI: 10.15252/msb.20156123
|View full text |Cite
|
Sign up to set email alerts
|

Time‐ and compartment‐resolved proteome profiling of the extracellular niche in lung injury and repair

Abstract: The extracellular matrix (ECM) is a key regulator of tissue morphogenesis and repair. However, its composition and architecture are not well characterized. Here, we monitor remodeling of the extracellular niche in tissue repair in the bleomycin-induced lung injury mouse model. Mass spectrometry quantified 8,366 proteins from total tissue and bronchoalveolar lavage fluid (BALF) over the course of 8 weeks, surveying tissue composition from the onset of inflammation and fibrosis to its full recovery. Combined ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
246
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(260 citation statements)
references
References 82 publications
(117 reference statements)
12
246
0
2
Order By: Relevance
“…These findings are consistent with previous reports in which both proteins were found to be up-regulated in mouse and rat models of bleomycin-induced pulmonary fibrosis (22)(23)(24). Schiller et al (23) showed that Tnc is increased at both the protein and mRNA levels in the lungs of mice treated with bleomycin, and demonstrated that higher Tnc expression is associated with stiffer lung tissue, a feature of fibrosis. Furthermore, Tnc not only is a marker of pulmonary fibrosis, but also has been implicated in the pathogenesis of the disease.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings are consistent with previous reports in which both proteins were found to be up-regulated in mouse and rat models of bleomycin-induced pulmonary fibrosis (22)(23)(24). Schiller et al (23) showed that Tnc is increased at both the protein and mRNA levels in the lungs of mice treated with bleomycin, and demonstrated that higher Tnc expression is associated with stiffer lung tissue, a feature of fibrosis. Furthermore, Tnc not only is a marker of pulmonary fibrosis, but also has been implicated in the pathogenesis of the disease.…”
Section: Discussionsupporting
confidence: 94%
“…Changes in ECM in Lung Fibrosis. Two recent studies have used proteomics to report changes occurring in bleomycin-induced fibrosis (22,23). Along with some overlapping findings, our study of the insoluble ECM has uncovered and quantified additional proteins.…”
Section: Discussionmentioning
confidence: 91%
“…For example, Decaris et al characterized the alterations in ECM turnover following bleomycin-induced lung fibrosis, and Talmi-Frank et al measured changes in lung ECM protein abundance in the context of influenza infection (22,23). Proteomic analysis of samples after differential extraction and from different soluble fractions has the potential to provide improved resolution of the matrisome based on lung compartment (24). …”
Section: Ecm Proteinsmentioning
confidence: 99%
“…In a recent study, Schiller et al . performed a comprehensive analysis of proteomic and transcriptomic changes in ECM following bleomycin-induced lung injury (24). Analysis of multiple time points, out to 56 days post-injury, and of multiple compartments of the lung, including soluble and insoluble fractions of total tissue and bronchoalveolar lavage fluid, provided a high-resolution data set to explore pathways involved in host response to injury.…”
Section: Ecm Proteinsmentioning
confidence: 99%
See 1 more Smart Citation